2017
DOI: 10.29082/ijnms.v1i1.33
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Cognitive Function and Decrease the Level of Stress in the Elderly with Brain Gym

Abstract: KeywordsThe decline in cognitive function in the elderly, which is part of the aging process can result in long-term memory problems and information processes, so it is often regarded as a stressor that causes stress and perceived as an adverse threat. Brain gym can improve memory, decreased emotional stress and the clearer mind. The aim of the study analyzed the effectiveness of brain gym in improving cognitive function and decreased the level of stress of elderly. Pre-experimental study of one group pretest-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
1
7
0
1
Order By: Relevance
“…It is in line with other studes that the brain gym has a significant effect on the improvement of cognitive function of the elderly (Amtonis & Fata, 2014;Ardian & Nuraini, 2018). Exercise in the brain gym stimulates the brain by releasing stress, increasing learning concentration, clearing the mind, improving memory and cognitive abilities such as alertness, concentration, and speed in the learning process (Azizah et al, 2017;Erwanto & Kurniasih, 2018).…”
Section: Effectiveness Of Brain Gym Cognitive Functionsupporting
confidence: 87%
“…It is in line with other studes that the brain gym has a significant effect on the improvement of cognitive function of the elderly (Amtonis & Fata, 2014;Ardian & Nuraini, 2018). Exercise in the brain gym stimulates the brain by releasing stress, increasing learning concentration, clearing the mind, improving memory and cognitive abilities such as alertness, concentration, and speed in the learning process (Azizah et al, 2017;Erwanto & Kurniasih, 2018).…”
Section: Effectiveness Of Brain Gym Cognitive Functionsupporting
confidence: 87%
“…These ndings suggest the anti-anxiety role of oxytocin. A previous study demonstrated that 8-week Brain Gym intervention signi cantly decreased anxiety levels in 68 elderly people 12 . We observed signi cant group difference in the change of oxytocin levels with or without controlled for the effect of baseline oxytocin levels, in which greater increases in oxytocin levels were observed in the intervention group compared with the control.…”
Section: Discussionmentioning
confidence: 94%
“…Brain Gym has been reported to reduce stress in elderly people 12 . Our ndings provide preliminary evidence on the stress reduction effect of Brain Gym by demonstrating a greater reduction of salivary cortisol levels after 10-week of Brain Gym intervention than the control in kindergarteners with special needs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations